Synthesis, characterization and biological activities evaluation of novel sulfanyl derivatives - Saraç, Kamuran; Orek, Cahit; Koparir, Metin (Informa UK Limited, 2019)
A novel series of 1-(3-Methyl-3-mesityl)-cyclobutyl-2-{[5-(2-fluorophenyl)-4-(aryl-alkyl)-4H-[1,2,4]triazol-3-yl]sulfanyl}-ethanone compounds were synthesized by a condensation reaction. The new compounds were characterized by elemental analyses, FT-IR and 1H, 13C NMR techniques. The antioxidant and antibacterial properties of the synthesized compounds were also investigated. The in vitro antioxidant and antibacterial activities of the newly synthesized compounds were measured, and they were found to exhibit significantly high antioxidant activity.